Effects of NaB2O4:Mn2+ and Ba2Li2Si2O7:Sn3+,Mn2+ phosphors and remote structure organizations on the white light-emitting diodes with quantum dots and phosphors - Phan Xuan Le; Le Nguyen Hoa Binh (Bulletin of Electrical Engineering and Informatics, 2021)
In order to increase the optical features of white light-emitting diodes (WLEDs), quantum dots (QDs) and phosphor materials have been proposed because of outstanding performance. The configuration of WLEDs with QDs layer and phosphor-silicone layer suggested placing these components separately to limit light loss, and enhance consistency at contact surface of QDs. In this research, the effects of QDs and phosphor on the performance of WLEDs are concluded through experiments. The emitted light and PL spectra were examined thoroughly, and infrared thermal imagers were applied to simulate the heat generation of an actual WLED device. The results show that with the configuration of 60 mA energy source, WLEDs which has the QDs-on-phosphor form attained luminous efficiency (LE) of 110 lm/W, with color rendering index (CRI) of Ra=92 and R9=80, whereas the WLEDs which has the phosphor-on-QDs form only has 68 lm/W in LE, Ra=57 and R9=24. Furthermore, WLEDs which has the QDs-on-phosphor form has less high temperature generated at the components’ conjunction in comparison to the counterpart, the peak generated heat in QDs-on-phosphor WLEDs is also lower and the heating capacity gap between 2 structures can go up to 12.3°C.